Effect of Tannic Acid Application on Durability of Bond of Etch and Rinse Adhesive Resins - Alireza Boruziniat; Mostafa Babazadeh; Mahshid Gifani; Monavar Nasirzadeh (Mashhad University of Medical Sciences, 2017)
Aim: To determine the effect of different concentrations and application times of tannic acid on bond strength to dentin. Materials and Methods: Occlusal surfaces of 180 human molars were randomly divided into two groups of immediate shear bond strength evaluation and evaluation after 2 months of storage in collagenase solution. Each group was divided into 10 subgroups according to the solutions applied: no additional treatment (control), chlorhexidine 2% (Positive control), tannic acid 20% (30s, 1 min, 3min, 5min) and Tannic acid 30% (30s, 1 min, 3 min, 5 min). Failure mode were assessed using a stereo-microscope. The data were statistically analyzed by One-way ANONA and Tukey's post hoc test. Results: There was no significant difference in immediate bond strength among experimental groups. However, after 2 months storage in collagenase solution, a significant difference was found among the groups.  Bond strengths of CHX and 20% TA applied for 3 minute were significantly higher than the control group. Conclusion: Use of tannic acid and chlorhexidine has no negative effect on immediate shear bond strength. However, their application significantly prevents compromised bond strength caused by storage in collagenase solution.